Pengembangan Bahan Ajar Berbasis Saintifik pada Tema Panas dan Perpindahannya di Kelas V Sekolah Dasar - Astri, Dinda; Sukmawarti, Sukmawarti (Indonesian Research Journal on Education, 2022)
This study aims to: (1) develop scientific-based teaching materials on the theme of heat and its transfer in class V SD, (2) describe the feasibility of scientific-based teaching materials to be developed on the theme of heat and its transfer in class V SD, (3) determine the response students towards scientificbased teaching materials on the theme of heat and its transfer in the fifth grade of elementary school. This research is a type of research and development using the ADDIE development model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were material expert validators, teaching materials design experts, learning experts (class V teachers) and fifth grade students. The instrument used to collect data is a questionnaire or questionnaire. The data analysis technique used in this research is descriptive qualitative and descriptive quantitative. Based on the analysis of the data obtained through the validity test of materialexperts, teaching materials design experts, teacher responses, and student responses. The results of the validation by material experts are 76% including the good/decent category. The results of the validation by teaching materials design experts are 78.4% including the good/decent category. The results of the validation of the fifth grade teacher's responses are 95% in the very good/very decent category, while for student responses, 88% is in the very good/very decent category. Based on the results of the percentage of material experts, teaching materials design experts, teacher responses andstudent responses, then calculated the average result is 84.24% included in the very good/very suitable category for use in the learning process.